Aggregation and coalescence of partially crystalline emulsion drops investigated using optical tweezers. Issue 31 (16th July 2019) - R. Otazo, Mariela; Ward, Rob; Gillies, Graeme; Osborne, Reuben S.; Golding, Matt; Williams, Martin A. K.
Abstract : Using optical tweezers to study the aggregation and arrested coalescence of partially crystalline oil drops. Abstract : The solid content of viscoelastic emulsion drops is known to affect their propensity for aggregation and their subsequent coalescence behaviour, where the balance between the drive to reduce surface tension and the straining of an internal viscoelastic network is able to create a plethora of stable partially-coalesced states. The latter has previously been elegantly demonstrated in synthetic systems, generated using oil containing different phase volumes of added solids, with micro-pipette experiments carried out on emulsion drops of several tens of microns in size. Herein we carry out experiments in the same spirit but aided by optical tweezers (OT) and using smaller micron-sized emulsion drops generated from milk fat. Given the size dependence of Brownian fluctuations and Laplace pressure the experimental investigation of these smaller drops is not necessarily a trivial extension of the previous work. The solid content of initially separated drops is controlled using a temperature-cycling regime in the sample preparation protocol, and subsequently the propensity for drops to remain joined or not after being brought into contact was examined. Aggregated pairs of drops were then subjected to an increase in temperature, either locally using a high-powered laser, or more globally using a custom-made Peltier temperature-controller. By heating to different degrees, the amount of fat crystals in the drops was able to be controlled, with progressively more compact partially-coalesced states, and eventually complete coalescence generated as the solid content was reduced. While in contrast to previous studies, the emulsion studied here was quite different in size and nature, and the solid content was controlled using temperature, the same underlying physics was nevertheless observed.